Coblation versus Diode Laser Tonsillectomy in Children: A Randomized Controlled Trial (Bangladesh Journal of Otorhinolaryngology, 2020)
Objective: This study aimed to compare the efficacy of diode laser and coblation tonsillectomy in paediatric patients in relation to operative time, amount of blood loss, post operative pain, healing of tonsillar fossa and returns to normal diet.Methods: A total of 200 patients ,100 for coblaton and 100 for diode laser, aged 3-12 years with recurrent tonsillitis with or without snoring and sleep apnoea were recruited. Participants were prospectively randomised to diode laser and coblation tonsillectomy. Operative time and blood loss were recorded. Pain was recorded by VAS or assessed by using analgesic.Results: The operative time were recorded 07-15 minutes,mean 10 minutes in coblation group and 12-20 minutes ,mean 14 minutes in laser group., Blood loss was recorded 0-15 ml mean 8 ml in coblation group and 10-25 ml mean 13.5 ml in diode laser group . However, at post-operative day seven, the diode laser tonsillectomy group had significantly higher pain scores compared with coblationtonsillectomy groups.Coblation group started normal soft diet on day 5 whereas diode laser started on day 8Conclusion: Coblation tonsillectomy is associated with less operative time and blood loss, early returns to normal diet and less pain score in comparison to Diode laser tonsillectomyBangladesh J Otorhinolaryngol; October 2017; 23(2): 140-145